Economics and Sociology: Marshall in Relation to the Thought of His Time - Parsons, Talcott (Quarterly Journal of Economics, 1932)
Introductory. I. Marshall and Max Weber on Capitalism, 317. II. The Main Lines of English Social Thought, 321. III. Marshall's Relation to the English Tradition, 330. IV. Economics and Sociology: Marshall's Difficulties, 336. V. Possible Alternatives to Marshall's position; (a) Pareto, 339, (b) Weber, 343. Conclusion, 345.